The impact of COVID-19 on kidney transplant activities in Brazil: a descriptive study - Passoni, Reginaldo; Gadonski, Bruno; Carvalho, Ariana Rodrigues da Silva; Freitas, Tainá Veras de Sanders; Peres, Luis Alberto Batista (São Paulo Medical Journal, 2023)
BACKGROUND: The coronavirus 19 (COVID-19) pandemic has reached services, systems, and world society. Despite its certified efficiency, the Brazilian National Transplant System is not exempt from the side effects of COVID-19. OBJECTIVE: To compare kidney transplantation activity registered in Brazil between the pandemic (2020) and pre-pandemic (2019) periods. DESIGN AND SETTING: A descriptive study was conducted in March 2021. The annual reports of the Brazilian Transplantation Registry for 2019 and 2020 were included in this study. METHODS: We conducted a descriptive study of kidney transplant activity in Brazil in 2019 and 2020. RESULTS: A 23.9% decrease in kidney transplants per million population was observed during the pandemic period (22.9 in 2020 versus 30.1 in 2019). Kidney transplants with a living donor (-58.8%) and in the North Region (-79.5%) experienced the greatest declines. The pandemic waiting list increased by 6.8%, and deaths during the waiting period increased by 36.8%. The number of patients on the waiting list and transplant teams decreased by 31.3% and 9.5%, respectively. CONCLUSION: The COVID-19 pandemic drastically affected Brazil and had a significant negative impact on KT activities in the country.